Comment le rapport au texte biblique transforme le rapport au texte littéraire au XVIIIe siècle : le cas Rousseau - Di Rosa, Geneviève (Quêtes littéraires, 2013)
In the 18th century, the Bible felt the full force of criticism by radical Enlightenment thinkers who read it piece by piece and denounced the process of its creation as an imposture – thus extending the break initiated by moral and historical critiques of the previous century. In doing so, they nevertheless failed to grant it the literary status of a “profane work”. Yet, Rousseau, who produced a literary rewriting of the Book of Judges with his Levite of Ephraim, pondered over the violence inflicted on biblical intertextuality during his exile in Môtiers: in his Letters Written from the Mountain, he compared it to the violence caused to his own literary works. By draw-ing this parallel, he opened a reflection on the different manners of reading a text, as well as the possibility of regulating the reader’s violence through proposing an ethics of literary reception. Analogy might not work as a substitute; however, it enabled Rousseau to go beyond the mistreatment which anti-philosophers or philosophers inflicted on his works, by giving, among other things, an autobiographical orienta-tion to his writing: one in which the author is ready to take responsibility for giving himself to the reader. The ambivalence of the sacred and the profane, the perception of a common essence of religion – defined either by sacrifice or gift – were thus what helped Rousseau invent the autobiographical pact.